2011
DOI: 10.3390/ph4040603
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-HT3 Receptors in the Antidepressant Response

Abstract: Serotonin (5-HT)3 receptors are the only ligand-gated ion channel of the 5-HT receptors family. They are present both in the peripheral and central nervous system and are localized in several areas involved in mood regulation (e.g., hippocampus or prefrontal cortex). Moreover, they are involved in regulation of neurotransmitter systems implicated in the pathophysiology of major depression (e.g., dopamine or GABA). Clinical and preclinical studies have suggested that 5-HT3 receptors may be a relevant target in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 198 publications
(276 reference statements)
0
53
0
Order By: Relevance
“…The 5-HT 3 receptor is the only pentameric ligand-gated cation channel of the 5-HT receptor family. Preclinical and clinical studies suggest that 5-HT 3 receptor antagonists may have antidepressant activity since they present antidepressant-like properties in preclinical tests (for review Bétry et al, 2011) and have also shown antidepressant and anxiolytic properties in humans (Lecrubier et al, 1993;McCann et al, 1997;Johnson et al, 2003;Piche et al, 2005;Harmer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT 3 receptor is the only pentameric ligand-gated cation channel of the 5-HT receptor family. Preclinical and clinical studies suggest that 5-HT 3 receptor antagonists may have antidepressant activity since they present antidepressant-like properties in preclinical tests (for review Bétry et al, 2011) and have also shown antidepressant and anxiolytic properties in humans (Lecrubier et al, 1993;McCann et al, 1997;Johnson et al, 2003;Piche et al, 2005;Harmer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that an important drug used for the clinical treatment of anxiety and depression, buspirone, is a full agonist of presynaptic and a partial agonist of postsynaptic 5-HT 1A receptors (Butkevich et al 2011). In addition, clinical and preclinical studies have suggested that 5-HT 3 receptors may be a relevant target in the treatment of affective disorders (Bétry et al 2011). Lastly, hippocampal MAO A and/or B activity as well as 5-HT 2A/2C receptors seem not be involved in the antidepressant-like action of (p-ClPhSe) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 3 R antagonists are used to effectively treat patients experiencing irritable bowel syndrome and chemotherapy-/radiotherapy-induced and postoperative nausea and vomiting (Thompson, 2007). Some antidepressants (Choi, 2003; Eisensamer, 2003) and antipsychotic drugs (Rammes, 2004) also antagonize 5-HT 3 R, which, together with other preclinical and clinical studies, suggest the relevance of 5-HT 3 R antagonism for treating psychiatric disorders (Bétry, 2011). We recently discovered that bupropion, another antidepressant, antagonizes 5-HT 3A R (Pandhare, 2017).…”
Section: Introductionmentioning
confidence: 89%